Numerical simulation of gas-dynamic stage of spark discharge in oxygen - Korytchenko, K.V.; Poklonskiy, E.V.; Vinnikov, D.V.; Kudin, D.V. (Вопросы атомной науки и техники, 2013)
A numerical model of gas-dynamic stage of spark discharge in oxygen that takes into consideration transient processes in an electric circuit and a change in the composition of gas-discharge atmosphere has been presented. The components of e, O, O₊, O₊₊ were considered for the conductive channel of a spark. The plasma ionization was neglected in the region beyond the conductive channel and the consideration was given to the components of O₂, O. The results of the distribution of thermodynamic parameters, spark channel resistance, radiation losses, and those of expenditure of discharge energy for dissociation and ionization have been given. Представлено математичну модель газодинамічної стадії розвитку іскрового розряду в кисні, що враховує перехідні процеси в електричному ланцюзі і зміну складу газорозрядного середовища. В області струмопровідного каналу розглядалися компоненти e, O, O₊, O₊₊. В області поза струмопровідного каналу іонізацією плазми нехтували, і розглядалися компоненти O₂, O. Представлено результати розподілу термодинамічних параметрів, опору іскрового каналу, втрат на випромінювання, витрат енергії розряду на іонізацію. Представлена математическая модель газодинамической стадии развития искрового разряда в кислороде, учитывающая переходные процессы в электрической цепи и изменение состава газоразрядной среды. В области токопроводящего канала рассматривались компоненты e, O, O₊, O₊₊. В области вне токопроводящего канала ионизацией плазмы пренебрегалось, и рассматривались компоненты O₂, O. Представлены результаты распределения термодинамических параметров, сопротивления искрового канала, потерь на излучение, затрат энергии разряда на ионизацию.